2020
DOI: 10.21037/atm.2020.02.161
|View full text |Cite
|
Sign up to set email alerts
|

Application of neural network model in assisting device fitting for low vision patients

Abstract: Background: To explore the application of neural network models in artificial intelligence (AI)-aided devices fitting for low vision patients.Methods: The data of 836 visually impaired people were collected in southwestern Fujian from May 2014 to May 2017. After a full eye examination, 629 low vision patients were selected from this group. Based on the visual functions, rehabilitation needs, and living quality scores of the selected patients, the professionals chose assistive devices that were the best fit for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…They also identified that acceptability in public spaces was a concern for many people. Dai et al 9 used artificial intelligence to identify which device can be predicted to suit each patient's needs in 629 Chinese low-vision individuals, including young adults and children and mostly from rural areas. They found that aids improving tasks at intermediate distance and listening aids were preferred and suggested that age, education, and the economic level should also be considered for prescription.…”
Section: Discussionmentioning
confidence: 99%
“…They also identified that acceptability in public spaces was a concern for many people. Dai et al 9 used artificial intelligence to identify which device can be predicted to suit each patient's needs in 629 Chinese low-vision individuals, including young adults and children and mostly from rural areas. They found that aids improving tasks at intermediate distance and listening aids were preferred and suggested that age, education, and the economic level should also be considered for prescription.…”
Section: Discussionmentioning
confidence: 99%
“…Low vision AIaided device fitting is closely related to visual rehabilitation needs. Dai et al [72] have established a FCNN model for AIaided device fitting. The accuracy of this AI model is about 80%.…”
Section: Artificial Intelligence Application In the Design Of Contact...mentioning
confidence: 99%
“…With the gradual diversification of AI technology, there have been many new tools (monitoring and remote management) in the field of nursing [106] . The AI-based medical devices can be helpful during patient recovery, meeting the requirements of rehabilitation and expediting the proceedings [107] . In addition, the application of AI robots also has accelerated limb rehabilitation in complex anthropopathic action guidance and helped patients to obtain a better degree of recovery [108,109] .…”
Section: Rehabilitation Assistancementioning
confidence: 99%